Altitudinal zonation of montane Quercus forests along two transects in Chirripó National Park, Costa Rica - Kappelle, Maarten (1995)
This paper is dedicated to the memory of Alwyn H. Gentry, an outstanding and inspiring tropical botanist who tragically died in a plane crash in the mountains of Ecuador on August 3 1993, when surveying possible boundaries for a new tropical cloud forest reserve.